2009
DOI: 10.1016/j.bbrc.2009.02.144
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale organization of β2-adrenergic receptor-Venus fusion protein domains on the surface of mammalian cells

Abstract: a b s t r a c tAdrenergic receptors are a key component of nanoscale multiprotein complexes that are responsible for controlling the beat rate in a mammalian heart. We demonstrate the ability of near-field scanning optical microscopy (NSOM) to visualize b 2 -adrenergic receptors (b 2 AR) fused to the GFP analogue Venus at the nanoscale on HEK293 cells. The expression of the b 2 AR-Venus fusion protein was tightly controlled using a tetracycline-induced promoter. Both the size and density of the observed nanosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…S1. PALM images yielded a number of ␤2 cluster features in the ϳ0.1-0.2/ m 2 range, which compares with ϳ1-1.4/m 2 from previous NSOM data (7,15). The presence of the endogenous ␤2 receptor in H9C2 cells in the clustered fraction, undetected by PALM, can lead to an underestimation in our data of the real clustering fraction.…”
Section: Plasma Membrane Distribution In Hela Cells Of the Nonclustersupporting
confidence: 53%
See 2 more Smart Citations
“…S1. PALM images yielded a number of ␤2 cluster features in the ϳ0.1-0.2/ m 2 range, which compares with ϳ1-1.4/m 2 from previous NSOM data (7,15). The presence of the endogenous ␤2 receptor in H9C2 cells in the clustered fraction, undetected by PALM, can lead to an underestimation in our data of the real clustering fraction.…”
Section: Plasma Membrane Distribution In Hela Cells Of the Nonclustersupporting
confidence: 53%
“…Because our goal was to compare ␤2 receptor clustering in different cell types, we also considered cardiomyocytes, such as H9C2 cells, derived from the embryonic rat heart, where the physiological role of the ␤2 receptor is well documented (31,32). In addition, in this cell line, a very high degree of receptor clustering was reported by means of NSOM measurements (7,15). When comparing the results from PALM with those from NSOM, the following considerations are taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These constraints have been addressed by expressing a fluorescent protein fusion (Venus-  AR) in HEK293 cells at variable expression levels. 37 The results showed that the number of small nanometer-sized clusters increased by a factor of ~3 with increased Venus-  AR expression level, but that their size was roughly constant with an average diameter of ~150 nm and with a   AR distribution in small nanometer-sized clusters. A second detailed quantitative study of membrane protein clustering visualized the distribution of a C-type lectin, DC-SIGN, that is involved in pathogen recognition for several viruses and other microorganisms.…”
Section: Membrane Receptors and Signaling Complexesmentioning
confidence: 85%
“…It was found that these receptors were organized in nanodomains with a diameter of ∼150 nm and did not reorganize upon agonist binding. 157,582 NSOM is nonetheless particularly difficult to implement in living cells. More recently, SMLM was used to re-evaluate the molecular density of the β 2 AR in cardiomyocytes, HeLa cells, and CHO cells.…”
Section: Membrane Organization Beyond the Diffraction Limitmentioning
confidence: 99%